Visualizing the Crowd Web-based Participatory Practices as Innovative Tools in drawing and mapping Milano Città Metropolitana - Villa, Daniele (DISEGNARECON, 2014)
Many new questions arise with regard to Web3.0- based technologies, which are more and more frequently used by non-experts to generate and share geographic information, new collective urban visions and place-based knowledge. This paper discusses the role of participatory planning and mapping practices in the context of Milan metropolitan region. In particular taking into account the collaborative use of new technologies (such as the use of microblogging and geo-social networks) within the processes of social sharing of the great urban transformations. Specific attention is given to the problems of perception and definition of shared landscape quality. In this context, the role of expert knowledge in the analysis and definition of the social perception of the urban landscape is now changing rapidly and radically.